Infographic Posters at Sumber Gentong Natural Tourism as an Information Medium - Hezron, Michael Patrick; Wardani, Lely Surya (IC-ITECHS, 2024)
Infographic posters have significant potential to enhance visitor understanding of the Sumber Gentong tourist destination. This study aims to analyze how infographics can be utilized as an effective visual communication tool to convey information about facilities, regulations, and conservation values at Sumber Gentong. Through engaging and informative visualizations, it is anticipated that infographics can increase Sumber Gentong's brand awareness, attract more visitors, and encourage active participation in environmental conservation.